Cable hoop convenient to fix

By using the optimized composition of galvanizing solution and hot-dip galvanizing technology on the cable hoop, a dense galvanizing layer is formed, which solves the problem of poor corrosion resistance of cable hoops, significantly improves corrosion resistance and service life, and reduces the plating rate.

CN119194329APending Publication Date: 2024-12-27RENQIU KAIHUA COMM POWER EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411364141.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-28
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing cable hoops have poor corrosion resistance, especially when used outdoors for a long time, which can affect the service life and may cause damage to the cable.

Method used

Using the optimized ingredients of galvanizing solution, including Al, Ni, Sn, Mo, Ce and other elements, a dense galvanizing layer is formed on the hoop matrix made of carbon steel through hot-dip galvanizing technology, and chlorine is added to the auxiliary plating solution. Components such as ammonium chloride, zinc chloride, sodium silicate and 3-methoxycyclohexyl formic acid improve the uniformity and adhesion of the galvanized layer and extend the service life of the cable clamp.

Benefits of technology

It significantly improves the corrosion resistance of the cable clamp, extends the service life, avoids damage to the cable due to rust or corrosion, and significantly improves the uniformity and adhesion of the galvanized layer, reducing the leakage plating rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of cable fasteners, and provides a cable hoop convenient to fix, the cable hoop comprises a hoop base body and a zinc coating arranged outside the hoop base body, and zinc plating liquid for the zinc coating is composed of, by weight, 0.05%-0.1% of Al, 0.5%-2.5% of Ni, 0.03%-0.05% of Sn, 0.05%-0.15% of Mo, 0.15%-0.3% of Ce and the balance Zn and inevitable impurities. According to the technical scheme, the problem that the corrosion resistance of the cable hoop is relatively poor in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cable fasteners, and in particular to a cable clamp that is easy to fix. Background Art

[0002] Cable clamps are devices that fix cables to poles, walls or other supporting structures to prevent them from shaking or shifting due to wind, vibration, etc. Cable clamps are usually made of metal materials, such as alloy steel, carbon steel, etc. Among these metal materials, alloy steel has higher strength and hardness, and is more resistant to wear and scratches during use, but it is more expensive; carbon steel has low cost, but relatively lower strength and hardness, and relatively poor corrosion resistance. When used outdoors for a long time, it is easy to rust or corrode, which not only affects the service life of the cable clamp, but may also cause damage to the cable. Therefore, it is urgent to develop a corrosion-resistant and easy-to-fix cable clamp. Summary of the invention

[0003] The present invention provides a cable clamp that is easy to fix, which solves the problem of relatively poor corrosion resistance of the cable clamp in the related art.

[0004] The technical solution of the present invention is as follows: The present invention provides a cable clamp that is easy to fix, comprising a clamp base and a galvanized layer arranged outside the clamp base, wherein the galvanizing liquid used for the galvanized layer is composed of the following components in weight percentage: Al 0.05%~0.1%, Ni 0.5%~2.5%, Sn 0.03%~0.05%, Mo 0.05%~0.15%, Ce 0.15%~0.3%, the balance is Zn and inevitable impurities.

[0005] As a further technical solution, it is composed of the following components in weight percentage: Al 0.06%~0.08%, Ni 0.5%~2%, Sn 0.04%~0.05%, Mo 0.05%~0.15%, Ce 0.15%~0.25%, the balance is Zn and inevitable impurities.

[0006] In the present invention, by optimizing the composition of the galvanizing solution, the uniformity and density of the galvanized layer are further improved, thereby further improving the corrosion resistance of the cable clamp.

[0007] As a further technical solution, in the composition of the zinc plating solution, the weight ratio of the Sn to the Mo is 1:1.5-2.5, for example, it can be 1:1.5, 1:2, 1:2.5, preferably 1:2.

[0008] In the present invention, when the weight ratio of Sn to Mo is 1:1.5-2.5, the corrosion resistance of the cable clamp is further improved.

[0009] In the present invention, the material of the clamp base is commercially available carbon steel, for example, Q195, Q235, Q275 or Q345.

[0010] In the present invention, by hot-dip galvanizing the carbon steel clamp base, the corrosion resistance of the cable clamp is improved, thereby extending the service life of the cable clamp and avoiding damage to the cable caused by rust or corrosion of the cable clamp when used outdoors for a long time.

[0011] The present invention also proposes a method for preparing the cable clamp that is easy to fix, comprising the following steps: hot-dip galvanizing the clamp substrate with a galvanizing liquid to obtain the cable clamp.

[0012] In the present invention, hot-dip galvanizing is performed at a temperature of 450-500° C. for a time of 60-120 seconds. By hot-dip galvanizing, a uniform and dense galvanized layer is formed on the surface of the clamp substrate, thereby improving the corrosion resistance of the cable clamp.

[0013] As a further technical solution, before the hot-dip galvanizing, the clamp substrate is subjected to a plating-assisting treatment using a plating-assisting solution, and the plating-assisting solution includes the following components in parts by weight: 50 to 70 parts of ammonium chloride, 30 to 50 parts of zinc chloride, 5 to 10 parts of sodium silicate, and 1 to 5 parts of cerium nitrate.

[0014] In the present invention, before hot-dip galvanizing, a plating-assisting liquid is first used to perform plating-assisting treatment on the clamp base, which can not only protect the clamp base before hot-dip galvanizing and prevent the surface oxidation of the clamp base, but also form a layer of salt film on the surface of the clamp base after the plating is completed, and improve the wettability of the clamp base and the uniformity of the zinc coating. Sodium silicate and cerium nitrate are added to the plating-assisting liquid, which improves the bonding force between the plating-assisting liquid and the clamp base and also improves the adhesion of the zinc coating, thereby further improving the corrosion resistance of the cable clamp.

[0015] As a further technical solution, the plating solution also includes 1 to 10 parts of 3-methoxycyclohexylcarboxylic acid.

[0016] In the present invention, 3-methoxycyclohexylcarboxylic acid is added to the plating solution, which further improves the bonding force between the plating solution and the clamp substrate, improves the wettability of the clamp substrate, reduces the plating leakage rate, and further improves the uniformity of the zinc plating layer and the corrosion resistance of the cable clamp.

[0017] As a further technical solution, the mass ratio of the 3-methoxycyclohexylcarboxylic acid to the cerium nitrate is 1.5:1.

[0018] In the present invention, when the mass ratio of 3-methoxycyclohexylcarboxylic acid to cerium nitrate is 1.5:1, the wettability of the clamp substrate is further improved, the plating leakage rate is reduced, and the uniformity of the zinc plating layer and the corrosion resistance of the cable clamp are further improved.

[0019] As a further technical solution, the following steps are included: the clamp base is subjected to degreasing, derusting and water washing treatment in sequence, then added to a plating aid solution for plating aid treatment, and after drying, is placed in a galvanizing solution for hot-dip galvanizing to obtain a cable clamp.

[0020] In the present invention, the clamp base is first placed in a sodium hydroxide solution with a mass concentration of 10% and soaked for 30-60 minutes, and then placed in a hydrochloric acid solution with a mass concentration of 10% and soaked for 30-60 minutes to perform degreasing and rust removal treatment, and then the treated clamp base is placed in flowing clean water for rinsing, and after drying, the clamp base after degreasing and rust removal water washing treatment is obtained, and the clamp base is immersed in a plating aid solution and soaked for 30-60 minutes, then taken out and dried to obtain the clamp base after the plating aid treatment, and then placed in a galvanizing solution for hot-dip galvanizing at a temperature of 450-500° C. and a time of 60-120 seconds to obtain a cable clamp.

[0021] The working principle and beneficial effects of the present invention are: In the present invention, by optimizing the composition of the galvanizing solution, Ni, Sn, Mo, Ce and other components are added to the galvanizing solution, so that the galvanizing solution forms a dense galvanized layer on the surface of the clamp substrate, thereby improving the corrosion resistance of the cable clamp. The Al content in the galvanizing solution is adjusted to cooperate with Ni, Sn, Mo and Ce in the galvanizing solution to further improve the corrosion resistance of the cable clamp. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] In the following embodiments and comparative examples, the material of the clamp base is Q345 carbon steel with a thickness of 2.5 mm, and the thickness of the galvanized layer is 15 μm.

[0024] Example 1 A cable clamp that is easy to fix is ​​prepared by the following method: First, the clamp substrate is immersed in a sodium hydroxide solution with a mass concentration of 10% for 60 minutes, and then immersed in a hydrochloric acid solution with a mass concentration of 10% for 30 minutes for degreasing and rust removal. The treated clamp substrate is then placed in running clean water for rinsing. After drying, the clamp substrate after degreasing and rust removal is obtained. The clamp substrate is immersed in a plating aid solution for 30 minutes, then taken out and dried to obtain the clamp substrate after plating aid treatment. The clamp substrate is placed in a galvanizing solution for hot-dip galvanizing at a temperature of 450°C for 120 seconds to obtain a galvanized layer with a weight of 1000 %.

[0025] The zinc plating solution is composed of the following components in mass percentage: Al 0.05%, Ni 0.5%, Sn 0.03%, Mo0.05%, Ce 0.15%, and the balance is Zn and unavoidable impurities; The plating solution comprises the following components in parts by weight: 50 parts of ammonium chloride, 50 parts of zinc chloride and 400 parts of water.

[0026] Example 2 A cable clamp that is easy to fix is ​​prepared by the following method: First, the clamp substrate is immersed in a sodium hydroxide solution with a mass concentration of 10% for 30 minutes, and then immersed in a hydrochloric acid solution with a mass concentration of 10% for 60 minutes for degreasing and rust removal. The treated clamp substrate is then rinsed in running clean water, and dried to obtain the clamp substrate after degreasing and rust removal and washing treatment. The clamp substrate is immersed in a plating aid solution for 60 minutes, then taken out and dried to obtain the clamp substrate after plating aid treatment, and placed in a galvanizing solution for hot-dip galvanizing at a temperature of 500°C for 60 seconds to obtain a cable clamp.

[0027] The zinc plating solution is composed of the following components in mass percentage: Al 0.1%, Ni 2.5%, Sn 0.05%, Mo0.15%, Ce 0.3%, and the balance is Zn and unavoidable impurities; The plating solution comprises the following components in parts by weight: 70 parts of ammonium chloride, 30 parts of zinc chloride and 400 parts of water.

[0028] Example 3 The difference between this embodiment and embodiment 1 is that the zinc plating solution consists of the following components in mass percentage: Al 0.06%, Ni 0.5%, Sn 0.04%, Mo 0.05%, Ce 0.15%, and the balance is Zn and unavoidable impurities.

[0029] Example 4 The difference between this embodiment and embodiment 1 is that the zinc plating solution consists of the following components in mass percentage: Al 0.08%, Ni 2%, Sn 0.05%, Mo 0.15%, Ce 0.25%, and the balance is Zn and unavoidable impurities.

[0030] Example 5 The difference between this embodiment and embodiment 1 is that the zinc plating solution consists of the following components in mass percentage: Al 0.06%, Ni 0.5%, Sn 0.04%, Mo 0.06%, Ce 0.15%, and the balance is Zn and unavoidable impurities.

[0031] Example 6 The difference between this embodiment and embodiment 1 is that the zinc plating solution consists of the following components in mass percentage: Al 0.06%, Ni 0.5%, Sn 0.04%, Mo 0.1%, Ce 0.15%, and the balance is Zn and unavoidable impurities.

[0032] Example 7 The only difference between this embodiment and embodiment 6 is that the plating solution includes the following components in parts by weight: 50 parts of ammonium chloride, 50 parts of zinc chloride, 10 parts of sodium silicate, 5 parts of cerium nitrate, and 400 parts of water.

[0033] Example 8 The only difference between this embodiment and embodiment 2 is that the plating solution includes the following components in parts by weight: 70 parts of ammonium chloride, 30 parts of zinc chloride, 5 parts of sodium silicate, 1 part of cerium nitrate, and 400 parts of water.

[0034] Example 9 The only difference between this embodiment and embodiment 7 is that the plating solution further includes 1 part of 3-methoxycyclohexylcarboxylic acid.

[0035] Example 10 The only difference between this embodiment and embodiment 7 is that the plating solution further includes 10 parts of 3-methoxycyclohexylcarboxylic acid.

[0036] Embodiment 11 The only difference between this embodiment and embodiment 7 is that the plating solution further includes 7.5 parts of 3-methoxycyclohexylcarboxylic acid.

[0037] Comparative Example 1 The only difference between this comparative example and Example 1 is that the mass percentage of Al in the zinc plating solution is 0.025%.

[0038] Comparative Example 2 The only difference between this comparative example and Example 1 is that the mass percentage of Al in the zinc plating solution is 0.15%.

[0039] Comparative Example 3 The only difference between this comparative example and Example 1 is that the zinc plating solution does not contain Sn.

[0040] Comparative Example 4 The only difference between this comparative example and Example 1 is that the zinc plating solution does not contain Mo.

[0041] The cable clamps prepared in Examples 1 to 11 and Comparative Examples 1 to 4 were subjected to corrosion resistance tests: the neutral salt spray test (NSS test) method specified in GB / T 10125-2012 "Artificial atmosphere corrosion test salt spray test" was carried out, and the test conditions were: temperature 35°C ± 2°C, 80cm 2 The average sedimentation rate of the horizontal area is 1.5mL / h±0.5mL / h, the concentration of the sodium chloride solution is 50g / L±5g / L, the pH value is 6.5~7.2, and the test time is 48h; the mass loss rate of the sample after the neutral salt spray test is calculated, and the calculation results are shown in Table 1: Table 1 Corrosion resistance test results

[0042] It can be seen from Table 1 that compared with Comparative Examples 1 to 4, the mass loss rate of the cable clamps of Examples 1 to 11 after the neutral salt spray test is greatly reduced, indicating that Examples 1 to 11 of the present invention improve the corrosion resistance of the cable clamp by adjusting the mass percentage of Al in the galvanizing solution to 0.05% to 0.15%, and adding Sn and Mo to the galvanizing solution also improves the corrosion resistance of the cable clamp.

[0043] Compared with Examples 1 to 4, the weight ratio of Sn to Mo in the galvanizing solution components was adjusted in Examples 5 to 6. As a result, the mass loss rate of the cable clamps in Examples 5 to 6 after the neutral salt spray test was lower than that in Examples 1 to 4, indicating that when the weight ratio of Sn to Mo in the galvanizing solution was 1:1.5 to 2.5, the corrosion resistance of the cable clamp was further improved.

[0044] Sodium silicate and cerium nitrate were added to the plating solution of Examples 7 and 8. As a result, the mass loss rate of the cable clamp of Example 7 after the neutral salt spray test was lower than that of Example 6. Similarly, the mass loss rate of the cable clamp of Example 8 after the neutral salt spray test was lower than that of Example 2, indicating that the addition of sodium silicate and cerium nitrate to the plating solution further improved the corrosion resistance of the cable clamp.

[0045] Compared with Example 6, 3-methoxycyclohexylcarboxylic acid was added to the plating solution of Examples 9 to 11, and the mass ratio of 3-methoxycyclohexylcarboxylic acid to cerium nitrate was adjusted. As a result, the mass loss rate of the cable clamps of Examples 9 to 11 after the neutral salt spray test was lower than that of Example 6, and the mass loss rate of the cable clamp of Example 11 after the neutral salt spray test was the lowest, indicating that the addition of 3-methoxycyclohexylcarboxylic acid to the plating solution further improved the corrosion resistance of the cable clamp. When the mass ratio of 3-methoxycyclohexylcarboxylic acid to cerium nitrate was 1.5:1, the corrosion resistance of the cable clamp was the best.

[0046] The copper sulfate test method was used to test the uniformity of the galvanized layer of the cable clamps of Examples 6 to 11. The test method was as follows: the sample was placed in a copper sulfate solution at 18±2°C and soaked for 1 minute, then the sample was taken out, rinsed with running water, and the black precipitate was removed with a soft brush, and then wiped dry with a clean cloth for the next etching. When red metallic copper appeared on the sample, the sample reached the etching end point, and the number of copper sulfate tests was counted (the etching when metallic copper appeared was not counted in the number of copper sulfate tests). The preparation method of the copper sulfate solution is as follows: 36g of copper sulfate pentahydrate was added to 100mL of distilled water, heated to dissolve, cooled to room temperature, 0.036g of copper hydroxide was added, stirred evenly, left to stand for more than 24h, filtered, and a copper sulfate solution was obtained.

[0047] The statistical results are shown in the following table: Table 2 Copper sulfate test times

[0048] (Note: When the number of copper sulfate tests in Example 11 was 15, no red metallic copper appeared on the sample, so the number of copper sulfate tests was ≥ 15) It can be seen from Table 2 that compared with Example 6, the copper sulfate test times of the cable clamps of Examples 7 to 8 are all increased, indicating that the addition of sodium silicate and cerium nitrate in the plating solution improves the uniformity of the zinc plating layer, thereby improving the corrosion resistance of the cable clamp.

[0049] Compared with Example 7, the number of copper sulfate tests of the cable clamps of Examples 9 to 11 increased, and the number of copper sulfate tests of Example 11 was the largest, indicating that the addition of 3-methoxycyclohexylcarboxylic acid to the plating solution further improved the uniformity of the zinc plating layer, thereby further improving the corrosion resistance of the cable clamp.

[0050] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A cable clamp that is easy to fix, characterized in that: It includes a clamp base and a galvanized layer arranged outside the clamp base, and the galvanizing solution used for the galvanized layer is composed of the following components in weight percentage: Al 0.05%~0.1%, Ni 0.5%~2.5%, Sn 0.03%~0.05%, Mo 0.05%~0.15%, Ce 0.15%~0.3%, the balance is Zn and inevitable impurities.

2. A cable clamp that is easy to fix according to claim 1, characterized in that: It is composed of the following ingredients in percentage by weight: Al 0.06%~0.08%, Ni 0.5%~2%, Sn 0.04%~0.05%, Mo 0.05%~0.15%, Ce 0.15%~0.25%, the balance is Zn and inevitable impurities.

3. The cable clamp for easy fixation according to claim 1, characterized in that: In the composition of the zinc plating solution, the weight ratio of the Sn to the Mo is 1:1.5-2.

5.

4. The cable clamp for easy fixation according to claim 1, characterized in that: In the composition of the zinc plating solution, the weight ratio of the Sn to the Mo is 1:

2.

5. The cable clamp for easy fixation according to claim 1, characterized in that: The material of the clamp base is Q195, Q235, Q275 or Q345.

6. A method for preparing a cable clamp that is easy to fix according to any one of claims 1 to 5, characterized in that: The following steps are involved: The clamp base is hot-dip galvanized in a galvanizing solution to obtain a cable clamp.

7. The method for preparing a cable clamp that is easy to fix according to claim 6, characterized in that: Before the hot-dip galvanizing, the clamp substrate is subjected to a plating-assisting treatment using a plating-assisting solution, wherein the plating-assisting solution comprises the following components in parts by weight: 50-70 parts of ammonium chloride, 30-50 parts of zinc chloride, 5-10 parts of sodium silicate, and 1-5 parts of cerium nitrate.

8. The method for preparing a cable clamp that is easy to fix according to claim 7, characterized in that: The plating assistant solution also includes 1 to 10 parts of 3-methoxycyclohexylcarboxylic acid.

9. The method for preparing a cable clamp that is easy to fix according to claim 8, characterized in that: The mass ratio of the 3-methoxycyclohexylcarboxylic acid to the cerium nitrate is 1.5:

1.

10. The method for preparing a cable clamp that is easy to fix according to claim 7, characterized in that: The following steps are involved: The clamp base is sequentially subjected to degreasing, derusting and water washing treatments, then added to a plating-assisting solution for plating-assisting treatment, and after drying, is placed in a galvanizing solution for hot-dip galvanizing to obtain a cable clamp.